A distributed control strategy for groups of robots with application in flocking - Xiang Li; Chuanchuan Wang; Chunyan Li (Scientific Reports)
Abstract This paper presents a distributed control strategy, named Triangle Formation (TF) algorithm, for a group of robots. The algorithm is based on a geometric approach and enables three neighboring robots to form an Equilateral Triangular Configuration (ETC). The TF algorithm is scalable since it is developed for a large group of robots by using a neighbor selection technique. To achieve obstacle avoidance by group, the algorithm is enhanced further by introducing an artificial physics model. A series of simulation studies have been conducted to observe the performance and the effectiveness of the TF algorithm. These empirical results show that group flocking with multi-ETC network in an unknown environment can be realized with the TF algorithm successfully.